Time-trial performance in world-class speed skaters after chronic nitrate ingestion - Richard, P.; Koziris, L. P.; Charbonneau, M.; Naulleau, C.; Tremblay, J.; Billaut, (International Journal of Sports Physiology and Performance, 2018)
Purpose: Nitrate supplementation can increase tolerance to high-intensity work rates; however, limited data exist on the recovery of performance. The authors tested whether 5 d of nitrate supplementation could improve repeated time-trial performance in speed skating. Methods: Using a double-blind, placebo-controlled, crossover design, 9 international-level short-track speed skaters ingested 1 high (juice blend, ~6.5 mmol nitrate; HI) or low dose (juice blend, ~1 mmol nitrate; LO) per day on days 1-4. After a double dose of either HI or LO on day 5, athletes performed 2 on-ice 1000-m time trials, separated by 35 min, to simulate competition races. Differences between HI and LO were compared with the smallest practically important difference. Results: Salivary [nitrate] and [nitrite] were higher in HI than LO before the first (nitrate: 81%, effect size [ES]: 1.76; nitrite: 72%, ES: 1.73) and second pursuits (nitrate: 81%, ES: 1.92; nitrite: 71%, ES: 1.78). However, there was no difference in performance in the first (LO: 90.92 [4.08] s; HI: 90.95 [4.06] s, ES: 0.01) or the second time trial (LO: 91.16 [4.06] s; HI: 91.55 [4.40] s, ES: 0.09). Plasma [lactate] measured after the trials (LO: 14.8 [1.1] mM; HI: 14.8 [1.2] mM, ES: 0.01) and at the end of the recovery period (LO: 9.8 [2.1] mM; HI: 10.2 [1.9] mM, ES: 0.05) was not different between treatments. Conclusion: Five days of high-dose nitrate supplementation did not change physiological responses and failed to improve single and repeated time-trial performances in world-class short-track speed skaters. These data suggest that nitrate ingestion up to 6.5 mmol does not enhance recovery from supramaximal exercise in world-class athletes.